O uso das tecnologias na educação básica: uma experiência com o PIBID de informática educacional - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
This article aims to reflect on basic education in the field of initial and continuing education, showing which skills, with the use of ICTs, teachers of elementary school I (1st to 5th grade) should have in the school context. The methodology used in the development of this work is based on action research, from which observation, workshops and pedagogical strategies were made using digital and conventional learning objects as resources to support the pedagogical practice within the classroom of a public school in Santarém / For. The study is the result of the reflections experienced in the scope of the Institutional Program of Initiation to Teaching Scholarships (PIBID), in the practices in the school space and in the formation of the future graduate of the degree in Educational Informatics of UFOPA. We conclude that technology has to be seen as a complement to the teaching-learning process, creating possibilities for pedagogical actions and enhancing new modes of knowledge and teaching in the face of social changes resulting from technological evolutions and their effects on basic education.
Keywords: Educação básica; Formação inicial e continuada; PIBID; Tecnologia digital; CNPQ:: CIÊNCIAS EXATAS E DA TERRA